2018
DOI: 10.1148/radiol.2017171157
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Breast Cancer: Prognostic Value of Peritumoral Edema Identified at Preoperative MR Imaging

Abstract: Purpose To determine the prognostic value of peritumoral edema identified at preoperative breast magnetic resonance (MR) imaging for disease recurrence in patients with invasive breast cancer. Materials and Methods Between January 2011 and December 2012, 353 women (median age, 49 years; range, 27-77 years) with invasive breast cancer who had undergone preoperative MR imaging and mastectomy or breast-conserving surgery were identified. Two radiologists independently reviewed peritumoral edema on the basis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(95 citation statements)
references
References 33 publications
5
85
2
3
Order By: Relevance
“…Several studies have demonstrated that the enhancement patterns of tumor-adjacent parenchyma in DCE-MRI were associated with chemotherapy response (14), local recurrence (15), and survival (16) in breast cancer. In a recent study (40) the grade of peritumoral edema identified in breast MRI has been independently associated with disease recurrence. In study by Zhou et al (41), it was demonstrated that the peritumoral stiffness assessed by ultrasound elastography of malignant breast lesions was higher than that of benign lesions.…”
Section: P-values Were Calculated By Using χ 2 Test or Wilcoxon Rank-mentioning
confidence: 98%
“…Several studies have demonstrated that the enhancement patterns of tumor-adjacent parenchyma in DCE-MRI were associated with chemotherapy response (14), local recurrence (15), and survival (16) in breast cancer. In a recent study (40) the grade of peritumoral edema identified in breast MRI has been independently associated with disease recurrence. In study by Zhou et al (41), it was demonstrated that the peritumoral stiffness assessed by ultrasound elastography of malignant breast lesions was higher than that of benign lesions.…”
Section: P-values Were Calculated By Using χ 2 Test or Wilcoxon Rank-mentioning
confidence: 98%
“…However, mucinous carcinoma, necrotic cancer, and metaplastic carcinoma can have high signal intensity on T2-weighted images (2). T2-weighted imaging also allows the depiction of perifocal or prepectoral edema within the breast, which improves lesion classification (lesions with edema are more often malignant) and is a poor prognostic sign in patients with known breast cancer (37,38). Several studies have reported that T2-weighted imaging increases the specificity for differentiation of benign and malignant lesions (39,40).…”
Section: T2-weighted Imagingmentioning
confidence: 99%
“…L YMPHOVASCULAR INVASION (LVI), defined as the infiltration of tumor cells into lymphatic or blood vessels at the periphery of the invasive carcinoma, 1 has been widely recognized as a negative prognostic factor in invasive breast cancer. [2][3][4][5][6] Studies have revealed that LVI status facilitates the selection of an optimal therapeutic strategy for individual breast cancer patients. [7][8][9][10][11] The extent of LVI is an important factor for predicting neoadjuvant chemotherapy (NAC) efficacy.…”
mentioning
confidence: 99%